(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2009)
Study of the mangrove oyster (Crassostrea sp) to reduce heavy metal (Cu) concentration on shrimp pond water and the black tiger shrimp’s (Penaeus monodon) body was conducted during ten days. Variable used in this research was the efficiency level of mangrove oyster as a treatment in the Cu contaminated waters to reduce the level of the Cu concentration. Survival and specific growth rate of shrimp were also observed and measured. Histological condition of the fish especially gills was also observed to determine the level of dama ge caused by Cu. The results showed that oysters (Crassostrea sp) were a proper type of organisms used as bio-treatment in reducing Cu not only in the shrimp pond water but also in the body of the shrimp.Oysters we re able to reduce heavy metals Cu concent ration up to 78% level to the normal level of heavy metal Cu for black tiger shrimp. Keywords: Mangrove Oyster, Shrimp, Efficiency Level, Copper